Диплом ІІ ступеня - Адаменко, Є. І. (Сумський державний університет, 2019)
Dyploma of 2 place of 2 Stage of Allucrainian students Olympiad
Dyploma of 2 place of 2 Stage of Allucrainian students Olympiad
Keywords: Olympiad, Electronics